Pubertal development, social factors, and delinquent involvement among South Korean male adolescents - Kweon, Hae Soo (International journal of law, crime and justice, 2017)
Despite the growing attention paid by Western criminologists to the effects of pubertal timing on youthful misconducts, criminology in the Asian context has been slow to incorporate both pubertal timing and its interplay with other social risk factors into its research agenda. To bridge this gap, the present study examines the mechanisms underlying the association between pubertal development and delinquency among a sample of South Korean male adolescents. The results indicate, as with Western findings, that early pubertal development does increase delinquent behaviors. The relationship is linear and partially mediated by parental attachment and risk-taking. Parental attachment also moderates the effects of early pubertal development on delinquency. Based on the results, implications for policy and research are discussed.